Youtube Sebagai Media Dakwah Santri Putri Pondok Pesantren Islam Nyai Zainab Shiddiq Jember (Akun YouTube @ppnyaizainabshiddiq6863) - Mukarromah, Hayatul; ., Dahliah (Program Studi Ilmu Komunikasi, 2023)
Nowadays, da'wah activities cannot only be carried out conventionally, but can be carried out through various media. One of them is through social media YouTube. YouTube is a popular and spectacular social media platform, which can upload or share videos. Da'wah on social media via YouTube channels has become a phenomenon that occurs among preachers. This is what makes researchers want to know how effective YouTube is as a medium for da'wah for female students at the Nyai Zainab Shiddiq Jember Islamic Islamic Boarding School. The focus of the research examined in this thesis is: (1) What is the effectiveness of YouTube as a medium for da'wah for female students at the Nyai Zainab Siddiq Jember Islamic boarding school? (2) How is the analysis of the da'wah messages conveyed by the female students of the Nyai Zainab Shiddiq Islamic Islamic Boarding School in Jember? Da'wah message delivered by the female students of the Nyai Zainab Shiddiq Jember Islamic Islamic Boarding School? The method in the research results uses qualitative research methods. The approach used is a qualitative approach with a descriptive type. Data collection techniques use interviews, observation and documentation. And the validity of the data uses technical triangulation and source triangulation. From the results of this research, the author can conclude that preaching using YouTube social media is very effective, because it can provide Islamic religious teachings through tausiyah given by preachers to students, alumni and also the wider community, apart from that it can also promote Islamic boarding schools through activities preaching, so that now without using bulletins the public can find out the preaching message conveyed by PPI female student Nyai Zainab Shiddiq Jember.